2009
DOI: 10.2527/jas.2008-1354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the behavioral and physiological responses of piglets to tail docking and ear notching1

Abstract: Neonatal piglets are often subject to potentially painful processing procedures such as tail docking and ear notching during the first few days after birth. However, these procedures may influence the development of suckling behavior and passive transfer of immunoglobulins, especially if done within the first day postpartum. The objective of this experiment was to compare the effects of processing piglets during the first 24 h versus at 3 d of age on suckling and pain-related behavior, the passive transfer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 21 publications
5
81
1
2
Order By: Relevance
“…Behaviour of piglets after castration Pain-related behaviours in our study decreased over time, independently of treatment, mostly because of a decrease of huddled-up behaviour. An age effect in behaviours was also described by Torrey et al (2009); they found that 1-day-old piglets trembled more compared with 3-day-old piglets. This underlines the importance of including control treatments in a study design.…”
Section: Discussionmentioning
confidence: 70%
“…Behaviour of piglets after castration Pain-related behaviours in our study decreased over time, independently of treatment, mostly because of a decrease of huddled-up behaviour. An age effect in behaviours was also described by Torrey et al (2009); they found that 1-day-old piglets trembled more compared with 3-day-old piglets. This underlines the importance of including control treatments in a study design.…”
Section: Discussionmentioning
confidence: 70%
“…By sampling blood before every procedure, we established an individual baseline cortisol value for each piglet. Only male piglets were included in the study, considering that there is no interaction between sex and tail docking or ear notching (Torrey et al, 2009) and castration is obviously only possible with male piglets. According to Mellor and Stafford (2004) the magnitude of a response should be assessed, that is both duration and maximum height.…”
Section: Discussionmentioning
confidence: 99%
“…As welfare topics become increasingly important, the scrutinising of these procedures must not be neglected. Several studies have evaluated castration and tail docking and the impact that these procedures have on the welfare of the piglets (Von Borell et al, 2009;Sutherland and Tucker, 2011), their physiological and behavioural responses (Zöls et al, 2006;Llamas Moya et al, 2008;Torrey et al, 2009), the economic consequences and alternative methods (Carroll et al, 2006;Kilchling, 2010;Sutherland et al, 2012). However, very few studies have evaluated the impact of ear tagging on pig welfare and none have compared the relative distress caused by ear tagging with other painful husbandry procedures (castration and tail docking) or examined the effect of analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…An example is the latency to the occurrence of a withdrawal or kicking movement when a limited area of the leg, shoulder or rump is subjected to a painful stimulus, for instance, by heating the skin locally with a laser beam (pigs: Jarvis et al, 1997;calves: Veissier et al, 2000;cows: Herskin et al, 2003). Avoidance and defensive behaviours, including leg and body movements as if animals were trying to avoid or escape the painful stimuli, were observed during castration (Marx et al, 2003), teeth resection and tail docking in young piglets (Noonan et al, 1994;Torrey et al, 2009). Similarly, dairy cows or growing calves jumped or kicked when subjected to hot-iron or liquid-nitrogen branding (Lay et al, 1992a;SchwartzkopfGenswein et al, 1998).…”
Section: Postural and Behavioural Indicatorsmentioning
confidence: 99%
“…For example, less suckling or feeding behaviour, social isolation, behavioural desynchronisation with littermates and/or less social interactions with the dam were observed in pigs after surgical castration (McGlone and Hellman, 1988;Hay et al, 2003;Llamas Moya et al, 2008) or tail docking (Torrey et al, 2009). Similarly in calves, reduction in feed intake was observed after castration (Fisher et al, 1996).…”
Section: Postural and Behavioural Indicatorsmentioning
confidence: 99%